Regulatory B10 cell development and function - Lykken, Jacquelyn M. (Int Immunol, 2015)
B cells are known to instigate and promulgate immune responses by producing antibodies and presenting antigens to T cells. However, a rare but potent B-cell subset in both humans and mice is capable of inhibiting immune responses through the production of the anti-inflammatory cytokine IL-10. Regulatory B cells do not express any unique combination of surface markers but instead represent a small population of B cells that have acquired the unique ability to produce IL-10. This numerically rare B-cell subset is therefore functionally referred to as ‘B10 cells’ to reflect both their molecular program and the fact that their anti-inflammatory effects in models of autoimmunity, infection and cancer are solely attributable to IL-10 production. As with most B cells, B10 cell development and function appear to be predominantly, if not exclusively, driven by antigen-receptor signals. Once generated, B10 cells respond to both innate and adaptive immune signals, with a requirement for antigen-specific local interactions with T cells to induce IL-10 production and to provide optimal immune suppression in mouse models of autoimmune disease. B10 cells therefore provide an antigen-specific mechanism for delivering IL-10 locally to sites of immune activation and inflammation. The ability of B10 cells to regulate innate and adaptive immune responses makes them an ideal therapeutic target for the treatment of many immune-related disorders.